2003
DOI: 10.1002/ppul.10297
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast does not protect against hyperoxia‐induced inhibition of alveolarization in newborn rats

Abstract: Impaired lung development has been demonstrated in neonatal animals exposed to hyperoxia. High lung cys-leukotriene levels may be a contributing factor towards the increase in oxygen toxicity. We investigated the effect of cysteinyl-leukotriene inhibition using the receptor antagonist, montelukast (MK, Singulair), on hyperoxia-induced changes in lung parenchymal structure in neonatal rat pups. Rat pups were exposed to 21% O(2) (air) or 50% O(2) (moderate hyperoxia) from days 1-14 after birth, and were administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The method is similar to that used by others estimating the alveolar development by a radial alveolar count (Emery and Mithal, 1960;Cooney and Thurlbeck, 1982). The number of intercepts with a straight line or the internal surface area is directly proportional to the number of intercepts with a linear chord (Jouvencel et al, 2003).…”
Section: Analytical Measurementsmentioning
confidence: 93%
“…The method is similar to that used by others estimating the alveolar development by a radial alveolar count (Emery and Mithal, 1960;Cooney and Thurlbeck, 1982). The number of intercepts with a straight line or the internal surface area is directly proportional to the number of intercepts with a linear chord (Jouvencel et al, 2003).…”
Section: Analytical Measurementsmentioning
confidence: 93%
“…These authors exposed rats to HCH for 1 month during the neonatal period, allowed them to recover in room air for a period of 3 months and then injected them with MCT. Whereas this rat model did develop more severe remodeling of pulmonary arteries upon MCT treatment, the fact that chronic hypoxia was administered during the neonatal period when the lung was still immature [20,21] may have introduced some bias with respect to adult PAH. In contrast with this previous report, we demonstrated that HCH+MCT treatment induced severe pulmonary hypertension and intimal thickening in adult rats.…”
Section: Discussionmentioning
confidence: 99%
“…For both montelukast and SC57461A, which are orally active, the intraperitoneal route of delivery was necessitated by an inability to safely perform daily gavage in newborn rats. For montelukast, dose-response studies (1, 5, or 10 mg/kg ip daily) were conducted, with the lowest dose based on a previous negative study in neonatal rats (1 mg/kg ip daily) (21). These studies demonstrated maximal inhibitory effect on lung CCL4 content at 10 mg/kg (data not shown).…”
Section: Methodsmentioning
confidence: 99%
“…In neonatal animals, LTB 4 receptor blockade prevented acute hyperoxic lung injury in preterm guinea pigs (37), and a 5-LPO inhibitor decreased lung inflammation and edema induced by saline lavage in newborn piglets (1). Inhibitors of 5-LPO or FLAP prevented inhibited alveolar development secondary to severe hyperoxia (6), whereas montelukast (a cysLT 1 R antagonist) had no effect on chronic neonatal lung injury secondary to moderate hyperoxia (21) in neonatal rats. In premature human infants with evolving BPD, LTB 4 and LTE 4 were increased in tracheal aspirate fluid (16) and urine (20,45), respectively.…”
mentioning
confidence: 99%